Submicroscopic genomic rearrangements change gene expression in T‐cell large granular lymphocyte leukemia. (9th April 2014) - Iżykowska, Katarzyna; Zawada, Mariola; Nowicka, Karina; Grabarczyk, Piotr; Kuss, Andreas W.; Weissmann, Robert; Busemann, Christoph; Ludwig, Wolf‐Dieter; Schmidt, Christian A.; Przybylski, Grzegorz K.
Abstract Objectives To better understand the molecular pathogenesis of T‐cell large granular lymphocyte leukemia (T‐LGL), we decided to search for those genetic alterations in T‐LGL patients and MOTN‐1 cell line (established from T‐LGL patient) that have an impact on gene expression and as a result can influence cell biology. Methods Multicolor fluorescence in situ hybridization (mFISH) analysis of the MOTN‐1 cell line was performed as well as paired‐end next‐generation sequencing (NGS; Illumina HiSeq2000) of this cell line and one T‐LGL patient. In addition, chosen 6q region was characterized in three T‐LGL patients using high‐resolution comparative genomic hybridization (FT‐CGH) and LM‐PCR. Gene expression was studied by RNA sequencing (RNAseq; SOLID5500). Results Rearrangements were detected within 1p and 2q in MOTN‐1 affecting expression of FGR, ZEB2, and CASP8, and within 6q in MOTN‐1 and one T‐LGL patient affecting MAP3K5 and IFNGR1. Nineteen genes, among them FOXN3, RIN3, AKT1, PPP2R5C, were overexpressed as a result of an amplification in 14q in one T‐LGL patient. Two novel fusion transcripts were identified: CASP8‐ERBB4 in MOTN‐1 and SBF1‐PKHD1L1 in T‐LGL patient. Conclusions This study showed that submicroscopic genomic rearrangements change gene expression in T‐LGL. Several genes involved in rearrangements were previously linked to cancer and survival pattern that characterizes T‐LGL cells.